Building Perinatal Pathology Research Capacity in Sub-Saharan Africa - Bebell, Lisa M.; Ngonzi, Joseph; Meier, Frederick A.; Carreon, Chrystalle Katte; Birungi, Abraham; Kerry, Vanessa B.; Atwine, Raymond; Roberts, Drucilla J. (Frontiers in Medicine, 2022)
Introduction: Over two million stillbirths and neonatal deaths occur in sub-Saharan Africa (sSA) annually. Despite multilateral efforts, reducing perinatal mortality has been slow. Although targeted pathologic investigation can often determine the cause of perinatal death, in resource-limited settings, stillbirths, early neonatal deaths, and placentas are rarely examined pathologically. However, the placenta is a key source of diagnostic information and is the main determinant of fetal growth and development in utero, influencing child health outcomes. Methods: In 2016, our collaborative intercontinental group began investigating infectious perinatal death and adverse child health outcomes in Uganda. We developed and initiated a 4-day combined didactic/practical curriculum to train health workers in placental collection, gross placental examination, and tissue sampling for histology. We also trained a local technician to perform immunohistochemistry staining. Results: Overall, we trained 12 health workers who performed gross placental assessment for > 1,000 placentas, obtaining > 5,000 formalin-fixed tissue samples for research diagnostic use. Median placental weights ranged from 425 to 456 g, and 33.3% of placentas were < 10th percentile in weight, corrected for gestational age. Acute chorioamnionitis (32.3%) and maternal vascular malperfusion (25.4%) were common diagnoses. Discussion: Through a targeted training program, we built capacity at a university affiliated hospital in SA to independently perform placental collection, gross pathologic examination, and placental tissue processing for histology and special stains. Our training model can be applied to other collaborative research endeavors in diverse resource-limited settings to improve research and clinical capacity and competency for diagnostics and management of stillbirth, neonatal death, and child health outcomes.
Keywords: Uganda; Placenta; Fetus; Histopathology; Histology; Outcomes; Pregnancy; Stillbirth